Comparing the incidence of trismus following mandibular third molar extraction after administration of chlorhexidine and normal saline - M. Jafari; Sh. Sharifzade (Tehran University of Medical Sciences, 1998)
In this double blind clinical survey, 40 healthy candidates of mandibular thir molar surgery were selected and randomly allocated into two groups of 20. First group was asked to administer Chlorhexidine 0.2% mouth wash prior to the operation while the other group used normal saline for 60 seconds before the surgery. Mouth opening was measured before surgery and in 1st, 3rd, 7th days following the operation. Statistical analysis revealed significantly more mouth opening (lower level of trismus) in patients utilizing chlorhexidine before surgery.